Shortest Distance Orientation Algorithm for Robot Path Planning using Low-Cost IR Sensor System - AL-Furati, Israa S.; Rashid, Abdulmuttalib T. (2020 International Conference on Electrical, Communication, and Computer Engineering (ICECCE), 2020)
This paper demonstrates a new algorithm in the path planning field for indoor robot navigation, focusing on finding the shortest and most safe path from the robot source position to its target. Robot localization matters are solved by using an IR transmitter fixed to the robot and a low-cost IR sensor array that is regularly distributed in the environment. The robot location depends on a group of IR receiver sensors that sense the IR transmitter signal where the location of each IR receiver is dependent on it is the location in the IR receivers array. The robot initial position is computed by using the modified binary search algorithm to scan the IR receivers array. A path planning problem is solved by using a new algorithm called the shortest distance orientation algorithm. A chain of the IR receivers within the sensing range of the virtual path is activated to be scan through the robot moves to the target. This process helps in reducing the localization time when the robot moves toward the target. At each step of the robot movement, it is direction is corrected dependent on the angle between its orientation and the direction of the line between its location and the target location. The simulation results for different types of IR array environments are shown good performance for this algorithm.